2017
DOI: 10.1002/cctc.201700726
|View full text |Cite
|
Sign up to set email alerts
|

A Titanium Dioxide Supported Gold Nanoparticle Catalyst for the Selective N‐Formylation of Functionalized Amines with Carbon Dioxide and Hydrogen

Abstract: A TiO2‐supported, gold nanoparticle catalyst was found to allow the N‐formylation of various amines, including normally unreactive anilines, by using CO2 as the carbonyl source under a H2 atmosphere. A series of reducible functional groups, such as olefins, halogens, carbonyls, carbamates, and cyano moieties, were completely retained during the formylation, which proved the highly selective nature of the formylation reaction. The catalyst was also found to be reusable without any loss of activity or selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 80 publications
1
52
0
Order By: Relevance
“…[19] After this seminalw ork, an umber of homogeneous and heterogeneous catalytic systemsh ave been reported. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In general, homogeneous complexes are more efficient catalysts and exhibit higher selectivity in an umber of transformations. In 2015, in the presence of 0.002 mol %R u-PNP pincerc omplex, Ding and co-workersh ave realizedt he efficients traightforward and practical N-formylation of dimethylamine in DMF at 120 8Cu nder CO 2 /H 2 atmosphere (35 atm for each, Scheme 1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19] After this seminalw ork, an umber of homogeneous and heterogeneous catalytic systemsh ave been reported. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In general, homogeneous complexes are more efficient catalysts and exhibit higher selectivity in an umber of transformations. In 2015, in the presence of 0.002 mol %R u-PNP pincerc omplex, Ding and co-workersh ave realizedt he efficients traightforward and practical N-formylation of dimethylamine in DMF at 120 8Cu nder CO 2 /H 2 atmosphere (35 atm for each, Scheme 1a).…”
mentioning
confidence: 99%
“…An umber of amines were convertedt ot heir corresponding formamides at 150 8C. [34] Despite of these achievements, air-sentive luxury phosphine ligands, high reaction temperature and high gas pressure are still hampered their praticala pplication in industry.A sh eterogeneous catalytic system is more suitable for the industrial DMF manufacturing, [35][36][37] in 2014, Shi and co-workers demonstrated Pd/Al 2 O 3 -NR-RDcatalystbydepositing palladium on as hape controllable Al 2 O 3 support exhibiting good activity in the catalytic N-formylation of aminesw ith CO 2 and H 2 (1 MPa CO 2 and 2MPa H 2 ,S cheme 1a)a t1 30 8C. And the Pd/ Al 2 O 3 -NR-RD catalysts are readily seperated via centrifugation, and 83 %y ield was maintained after reused for three times.…”
mentioning
confidence: 99%
“…The concept of coupling alcohols other than methanol, and amines for the synthesis of amides under Au nanoparticle-catalysis, has also been shown to be synthetically useful [ 34 , 35 ]. Finally, Au nanoparticle catalysis has also been used in the synthesis of formamides by other approaches, such as in the reaction of amines with CO 2 or ammonium formate under reductive conditions [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we proposed the mechanism of the Cu‐catalyzed formylation reaction in THF, where the salt (alkyl ammonium alkyl carbamate) served as the intermediate . Except for this reaction pathway, the route to N‐formylation reaction with CO 2 and H 2 through formic acid was also reported, where HCOOH is formed from the hydrogenation of CO 2 . In spite of the good performance with different catalysts in various solvents, the reports about the effect of the solvent on the performance of the reaction and the relation between the solvent and the mechanism is little up to now.…”
Section: Figurementioning
confidence: 99%
“…However, with the same amount HCOOH, the yield was only 16.3 % (Table , Entry 2). When we increased the amount of HCOOH to 2.5 mmol, we also gained high yield of the product (Table , Entry 3), which is consistent with the HCOOH‐mediated formylation reaction report . Besides, we compared the reaction rate using the same amount of HCOOH and HCOOCH 3 as C1 source in other solvents and other catalytic systems for the N‐formylation reaction.…”
Section: Figurementioning
confidence: 99%